Multifunctional nano-enzyme composite hydrogel as well as preparation method and application thereof

By developing a multifunctional nanoenzyme complex hydrogel, the complex of MoS2, cysteine ​​and galangin, the shortcomings in inhibiting ferrodysfunction and antibacterial in the treatment of periodontitis were solved, and effective local treatment of periodontitis was achieved.

CN119792190APending Publication Date: 2025-04-11ANHUI UNIVERSITY OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510041479.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The treatment of periodontitis faces challenges of complex pathological mechanisms and long-term maintenance treatment, especially in terms of deficiencies in inhibiting ferrous death and antibacterial treatment.

Method used

A multifunctional nanoenzyme composite hydrogel was developed to form SNCI@MLG by synthesizing a complex of molybdenum disulfide (MoS2) with cysteine ​​and galangin, and introducing ionic liquids into the hydrogel. This complex has the dual effects of antibacterial and inhibiting ferrous death.

Benefits of technology

This multifunctional nanoenzyme composite hydrogel not only has antibacterial properties, but also can effectively inhibit iron death, providing a new local treatment method for periodontitis, enhancing the effect and durability of the treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119792190A_ABST
    Figure CN119792190A_ABST
Patent Text Reader

Abstract

The invention discloses multifunctional nano-enzyme composite hydrogel as well as a preparation method and application thereof. The preparation method comprises the following steps: synthesizing molybdenum disulfide MoS2 by taking hexaammonium heptamolybdate tetrahydrate and thiourea as raw materials; the preparation method comprises the following steps: carrying out stirring reaction on MoS2 and cysteine to obtain MoS2-LC; the preparation method comprises the following steps: mixing galangin with MoS2-LC, carrying out ultrasonic treatment, and carrying out a stirring reaction to obtain MoS2-LC (at) Gal; the preparation method comprises the following steps: adding acetic anhydride into a carboxymethyl chitosan aqueous solution to obtain N-acetylated carboxymethyl chitosan N-CC; the preparation method comprises the following steps: adding 1-butyl-3-methylimidazole chlorine salt into N-CC to react, and carrying out alcohol precipitation to obtain N-CC-IL; a cross-linking agent, MoS2-LC (at) Gal and N-CC-IL are subjected to a blending reaction, and SNCI (at) MLG is obtained. Pharmacodynamic results show that the multifunctional nano-enzyme composite hydrogel prepared by the preparation method disclosed by the invention can play a role in inhibiting ferroptosis while having an antibacterial effect, and a new possibility is provided for periodontal local treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of medical technology, and in particular to a multifunctional nanoenzyme composite hydrogel and a preparation method and application thereof. Background Art

[0002] Periodontitis is a chronic inflammatory disease caused by bacteria that mainly affects the supporting tissues around the teeth, including the gums, periodontal ligament, alveolar bone, and periodontal membrane. Its pathogenesis usually progresses from gingivitis, and if not controlled, it may eventually lead to tooth loss. The occurrence and development of periodontitis are closely related to a variety of factors, among which bacterial infection, host immune response, genetic susceptibility, and lifestyle all play an important role. Although the treatment of periodontitis continues to develop, its pathological mechanism is complex and treatment strategies still face many challenges. The clinical symptoms of periodontitis usually include gingival bleeding, gingival swelling, loose teeth, bad breath, and gingival recession. The treatment goals of periodontitis are to control infection, reduce inflammation, restore periodontal tissue function, and prevent recurrence. Treatment methods include scaling, root planing, antibiotics, and surgical treatment. Although significant progress has been made in clinical treatment methods, long-term maintenance treatment is still the key to preventing the recurrence of periodontitis. Further in-depth development of new preparations for the treatment of periodontitis will provide new directions for future prevention and treatment.

[0003] Ferroptosis is a type of programmed cell death first proposed by Brent R. Stockwell of Columbia University in 2012. It is characterized by iron dependence and lipid peroxidation. Unlike traditional apoptosis, necrosis or autophagy, ferroptosis is mainly triggered by the generation of reactive oxygen species (ROS) catalyzed by iron ions and the accumulation of lipid peroxides caused by the decrease in the activity of glutathione peroxidase 4 (GPX4). Studies in recent years have shown that ferroptosis plays an important role in the occurrence and development of periodontitis. Abnormal expression of ferroptosis-related genes and proteins may lead to the death of periodontal tissue cells and the destruction of alveolar bone, thereby aggravating the condition of periodontitis. Therefore, in-depth research on the mechanism of ferroptosis in periodontitis is expected to provide new ideas and methods for the treatment of periodontitis.

[0004] Therefore, it is necessary to research and develop a periodontal local drug delivery system that can inhibit periodontitis ferroptosis and have good antibacterial activity, providing a new idea for the treatment of periodontitis. Summary of the invention

[0005] In view of this, the primary purpose of the present invention is to provide a method for preparing a multifunctional nanozyme composite hydrogel. The nanozyme composite hydrogel prepared by this method can inhibit ferroptosis while having antibacterial effects, providing a new direction for the local treatment of periodontitis.

[0006] The present invention is achieved through the following technical solutions:

[0007] A method for preparing a multifunctional nanozyme composite hydrogel comprises the following steps:

[0008] (1) Molybdenum disulfide MoS2 is synthesized using hexaammonium heptamolybdate tetrahydrate and thiourea as raw materials;

[0009] (2) stirring and reacting MoS2 and cysteine ​​to obtain MoS2-LC;

[0010] (3) mixing galangin with MoS2-LC, and stirring after ultrasonication to obtain MoS2-LC@Gal;

[0011] (4) adding acetic anhydride to the carboxymethyl chitosan aqueous solution to obtain N-acetylated carboxymethyl chitosan N-CC;

[0012] (5) adding 1-butyl-3-methylimidazolium chloride to N-CC for reaction, followed by alcohol precipitation to obtain N-CC-IL;

[0013] (6) The crosslinker, MoS2-LC@Gal and N-CC-IL are blended to obtain SNCI@MLG.

[0014] Preferably, in step (2), the mass ratio of MoS2 to cysteine ​​is 1:3-10.

[0015] Preferably, the specific steps of step (3) are: dissolving MoS2-LC in water to form liquid A, dissolving galangin in a co-solvent to form liquid B, mixing liquid A and liquid B, and stirring the mixture after ultrasonication to obtain MoS2-LC@Gal.

[0016] Preferably, the co-solvent is methanol: water = 1:1, ethanol: water = 1:1 or dichloromethane: water = 1:1; the ultrasonic time is 20-40 min.

[0017] Preferably, in step (4), the mass ratio of the carboxymethyl chitosan to acetic anhydride is 1:2-6.

[0018] Preferably, in step (5), the mass ratio of N-CC to 1-butyl-3-methylimidazolium chloride is 1:1-10.

[0019] Preferably, in step (5), the reaction conditions are 60° C.-80° C. and nitrogen for 36-72 hours.

[0020] Preferably, in step (6), the cross-linking agent is one or more of azobenzene, 4-(4-methoxyphenylvinyl)pyridine, selenocystamine or 7-diethylamino-4-thiocoumarylmethyl derivatives.

[0021] The present invention also provides a multifunctional nanoenzyme composite hydrogel, which is prepared by the above-mentioned preparation method.

[0022] The present invention also provides the use of the multifunctional nanoenzyme composite hydrogel in the preparation of a drug for treating periodontitis.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention adds cysteine ​​(L-cysteine, LC) on the basis of preparing MoS2 nanozyme, and uses the unique thiol group in LC to produce complexation with ferrous ions, thereby achieving the effect of adsorbing ferrous ions. In addition, the introduction of ionic liquid into the hydrogel not only retains the three-dimensional network structure of the hydrogel, but also further improves the antibacterial properties of the hydrogel. The efficacy results show that the multifunctional nanozyme composite hydrogel prepared by the present invention has an antibacterial effect and can play a role in inhibiting ferroptosis, providing a new possibility for local periodontal treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The scanning electron microscope and transmission electron microscope images of MoS2 in the embodiment of the present invention are shown;

[0026] Figure 2 The particle size of MoS2-LC@Gal and the potential diagram of MoS2, MoS2-LC, and MoS2-LC@Gal in the embodiment of the present invention;

[0027] Figure 3 It is the enzyme activity diagram of MoS2-LC@Gal in the embodiment of the present invention;

[0028] Figure 4 : is the nuclear magnetic resonance hydrogen spectrum of CC, N-CC, and N-CC-IL in the embodiments of the present invention;

[0029] Figure 5 The scanning electron microscope images of N-CC and N-CC-IL in the embodiments of the present invention are shown;

[0030] Figure 6 Graph showing viscosity and ductility of SNCI@MLG in an embodiment of the present invention;

[0031] Figure 7 This is a bacterial plate image of N-CC and N-CC-IL in the embodiments of the present invention;

[0032] Figure 8 The bacterial SEM images of N-CC and N-CC-IL in the embodiments of the present invention;

[0033] Fig. 9 The effects of MoS2 and MoS2-LC on ferrous ions in the embodiments of the present invention;

[0034] Fig.10 The changes in the level of periodontal inflammation in rats with periodontitis after the gel in the embodiment of the present invention was applied;

[0035] Fig.11 The changes of periodontal iron death-related indicators in rats with periodontitis after the gel was applied in the examples of the present invention. DETAILED DESCRIPTION

[0036] The present invention is further described below by means of specific implementation methods. The following examples are preferred implementation methods of the present invention, but the implementation methods of the present invention are not limited to the following examples.

[0037] The raw materials used in the embodiments of the present invention are all commercially available.

[0038] Embodiment 1:

[0039] A method for preparing a multifunctional nanozyme composite hydrogel specifically comprises the following steps:

[0040] (1) Preparation of MoS2

[0041] Dissolve 1 mmol hexaammonium heptamolybdate tetrahydrate and 42 mmol thiourea NH2CSNH2 in 60 mL deionized water. Stir the solution at room temperature for 30 min to dissolve all components and transfer it to a high-pressure reactor to react in a 200°C oven for 18 h. Collect the black precipitate, wash it with ethanol and deionized water alternately and centrifuge it several times to remove unreacted impurities, then place it in a 60°C vacuum drying oven to remove the solvent, and then obtain molybdenum disulfide (MoS2) with uniform morphology;

[0042] The results of scanning electron microscopy and transmission electron microscopy showed that the prepared MoS2 nanozyme was uniformly flower-shaped, which was mainly formed by self-assembly and curling stacking of nanosheets ( Figure 1 );

[0043] (2) Preparation of MoS2-LC

[0044] MoS2 and cysteine ​​(LC) were dissolved in 2 mL of deionized water at a mass ratio of 1:5 and stirred overnight, and MoS2-LC was obtained after washing;

[0045] (3) Preparation of MoS2-LC@Gal

[0046] MoS2-LC (1.0 mg / ml) was ultrasonically dissolved in water to form liquid A, and galangin was dissolved in CHCl2:H2O=1:1 to obtain 1.0 mg / ml to form liquid B; liquid A and liquid B were mixed, stirred overnight, centrifuged, and the supernatant was discarded to obtain MoS2-LC@Gal;

[0047] The particle size and potential were measured using a Malvern particle size analyzer. Figure 2 As shown, the particle size of MoS2-LC@Gal is about 300nm and the potential is about -20mV.

[0048] (4) Preparation of N-CC

[0049] At room temperature, carboxymethyl chitosan (CC, 0.6 g) was dissolved in distilled water (25 mL), and the solution was diluted with methanol (25 mL); acetic anhydride (1.6905 g) was added dropwise to the CC solution, and the mixture was stirred continuously at room temperature for 24 h. After the reaction was completed, the crude product was collected by acetone precipitation, dialyzed for 48 h, and freeze-dried for 48 h to obtain N-acetylated carboxymethyl chitosan (N-CC);

[0050] (5) Preparation of N-CC-IL

[0051] N-acetylated carboxymethyl chitosan (N-CC, 500 mg) was dissolved in deionized water (60 mL) and fully swollen overnight. 1-butyl-3-methylimidazolium chloride (1.5 g) was added to the above solution and reacted at 75°C under nitrogen protection for 40 h. After the reaction, the crude product was collected by ethanol precipitation, washed several times with anhydrous ethanol (3500 r / min, 10 min), and vacuum dried for 24 h to obtain N-CC-IL;

[0052] H NMR spectrum results ( Figure 4 ) represents the signal of D2O, and the peak at 1.95ppm represents the signal of methyl on the acetyl group; the new peak at 8.54ppm reflects the formation of hydrogen bonds within the N-CC-IL molecule compared with N-CC, and also confirms the successful preparation of N-CC-IL. Scanning electron microscopy results show that both N-CC and N-CC-IL have a three-dimensional network of hydrogels ( Figure 5 );

[0053] (6) Preparation of SNCI@MLG

[0054] MoS2-LC@Gal (10 mg), N-CC-IL (250 mg), and selenocystamine (500 mg) were weighed and dissolved in 2.5 mL of deionized water at 60 ° C for 6-8 h. After the reaction, dialyze using a dialysis membrane (MWCO: 8-14 kDa) for 48 h. The obtained product was freeze-dried for 48 h to obtain SNCI@MLG.

[0055] Embodiment 2:

[0056] A method for preparing a multifunctional nanozyme composite hydrogel specifically comprises the following steps:

[0057] (1) Preparation of MoS2

[0058] Dissolve 5 mmol hexaammonium heptamolybdate tetrahydrate and 150 mmol thiourea NH2CSNH2 in 60 mL deionized water. Stir the solution at room temperature for 30 min to dissolve all components and transfer it to a high-pressure reactor to react in a 200°C oven for 18 h. Collect the black precipitate, wash it with ethanol and deionized water alternately and centrifuge it several times to remove unreacted impurities, then place it in a 60°C vacuum drying oven to remove the solvent, and then obtain molybdenum disulfide (MoS2) with uniform morphology;

[0059] (2) Preparation of MoS2-LC

[0060] MoS2 and cysteine ​​(LC) were dissolved in 2 mL of deionized water at a mass ratio of 1:7 and stirred overnight, and MoS2-LC was obtained after washing;

[0061] (3) Preparation of MoS2-LC@Gal

[0062] MoS2-LC (1.0 mg / ml) was dissolved in water by ultrasonication to form liquid A, and galangin was dissolved in methanol: water = 1:1 to obtain 1.0 mg / ml to form liquid B; liquid A and liquid B were mixed, stirred overnight, centrifuged, and the supernatant was discarded to obtain MoS2-LC@Gal;

[0063] (4) Preparation of N-CC

[0064] At room temperature, carboxymethyl chitosan (CC, 0.6 g) was dissolved in distilled water (25 mL), and the solution was diluted with methanol (25 mL); acetic anhydride (3.6 g) was added dropwise to the CC solution, and the mixture was stirred continuously at room temperature for 24 h. After the reaction was completed, the crude product was collected by acetone precipitation, dialyzed for 48 h, and freeze-dried for 48 h to obtain N-acetylated carboxymethyl chitosan (N-CC);

[0065] (5) Preparation of N-CC-IL

[0066] N-acetylated carboxymethyl chitosan (N-CC, 500 mg) was dissolved in deionized water (60 mL) and fully swollen overnight. 1-butyl-3-methylimidazolium chloride (5.0 g) was added to the above solution and reacted at 80°C under nitrogen protection for 36 hours. After the reaction, the crude product was collected by ethanol precipitation, washed several times with anhydrous ethanol (3500 r / min, 10 min), and vacuum dried for 24 hours to obtain N-CC-IL;

[0067] (6) Preparation of SNCI@MLG

[0068] MoS2-LC@Gal (10 mg), N-CC-IL (250 mg), and selenocystamine (500 mg) were weighed and dissolved in 2.5 mL of deionized water at 60 ° C for 6-8 h. After the reaction, dialyze using a dialysis membrane (MWCO: 8-14 kDa) for 48 h. The obtained product was freeze-dried for 48 h to obtain SNCI@MLG.

[0069] Embodiment 3:

[0070] A method for preparing a multifunctional nanozyme composite hydrogel specifically comprises the following steps:

[0071] (1) Preparation of MoS2

[0072] Dissolve 5 mmol hexaammonium heptamolybdate tetrahydrate and 140 mmol thiourea NH2CSNH2 in 60 mL deionized water. Stir the solution at room temperature for 30 min to dissolve all components and transfer it to a high-pressure reactor to react in a 200°C oven for 18 h. Collect the black precipitate, wash it with ethanol and deionized water alternately and centrifuge it several times to remove unreacted impurities, then place it in a 60°C vacuum drying oven to remove the solvent, and then obtain molybdenum disulfide (MoS2) with uniform morphology;

[0073] (2) Preparation of MoS2-LC

[0074] MoS2 and cysteine ​​(LC) were dissolved in 2 mL of deionized water at a mass ratio of 1:10 and stirred overnight, and MoS2-LC was obtained after washing;

[0075] (3) Preparation of MoS2-LC@Gal

[0076] MoS2-LC (1.0 mg / ml) was dissolved in water by ultrasonication to form liquid A, and galangin was dissolved in ethanol: water = 1:1 to obtain 1.0 mg / ml to form liquid B; liquid A and liquid B were mixed, stirred overnight, centrifuged, and the supernatant was discarded to obtain MoS2-LC@Gal;

[0077] (4) Preparation of N-CC

[0078] At room temperature, carboxymethyl chitosan (CC, 1.1 g) was dissolved in distilled water (25 mL), and the solution was diluted with methanol (25 mL); acetic anhydride (4.5 g) was added dropwise to the CC solution, and the mixture was stirred continuously at room temperature for 24 h. After the reaction was completed, the crude product was collected by acetone precipitation, dialyzed for 48 h, and freeze-dried for 48 h to obtain N-acetylated carboxymethyl chitosan (N-CC);

[0079] (5) Preparation of N-CC-IL

[0080] N-acetylated carboxymethyl chitosan (N-CC, 250 mg) was dissolved in deionized water (60 mL) and fully swollen overnight. 1-butyl-3-methylimidazolium chloride (1.25 g) was added to the above solution and reacted at 60°C under nitrogen protection for 72 hours. After the reaction, the crude product was collected by ethanol precipitation, washed several times with anhydrous ethanol (3500 r / min, 10 min), and vacuum dried for 24 hours to obtain N-CC-IL;

[0081] (6) Preparation of SNCI@MLG

[0082] MoS2-LC@Gal (10 mg), N-CC-IL (250 mg), and selenocystamine (500 mg) were weighed and dissolved in 2.5 mL of deionized water at 60 ° C for 6-8 h. After the reaction, dialyze using a dialysis membrane (MWCO: 8-14 kDa) for 48 h. The obtained product was freeze-dried for 48 h to obtain SNCI@MLG.

[0083] Example 4: Process Optimization

[0084] The present invention investigates the MoS2-LC ratio, galangin dosage, and ultrasonic time by a single factor investigation method, and the results are shown in Tables 1-3 below:

[0085] Table 1 Effects of different ratios of MoS2:LC on the particle size, potential and drug loading of nanoparticles (n=3, mean±SD)

[0086]

[0087] It can be seen from Table 1 that when the ratio of MoS2:LC increases, the drug loading of the nanoparticles gradually decreases. Therefore, the preferred MoS2:LC mass ratio is 1:3-1:10. When the MoS2:LC ratio is 1:5, the drug loading is the highest. It can also be seen from the particle size of the nanoparticles in the table that the particle size is the smallest at this time. Therefore, the more preferred MoS2:LC mass ratio is 1:5.

[0088] Table 2 Effects of different galangin contents on nanoparticle size, potential, and drug loading (n=3, mean±SD)

[0089]

[0090] It can be seen from Table 2 that when the input amount of galangin is between 5-15 mg, the drug loading of the nanoparticles first increases and then decreases as the input ratio increases, so the input amount of galangin is selected to be 5-15 mg, preferably 10 mg.

[0091] Table 3 Effects of different ultrasound times on nanoparticle size and drug loading (n=3, mean±SD)

[0092]

[0093] It can be seen from Table 3 that as the ultrasonic time increases, the drug loading of the nanoparticles gradually increases. Therefore, the ultrasonic time is preferably set to 20-40 min, and more preferably to 30 min.

[0094] The MoS2, MoS2-LC, MoS2-LC@Gal, N-CC, N-CC-IL, and SNCI@MLG prepared in Example 1 were subjected to the following tests.

[0095] Test Example 1: Performance Investigation

[0096] (1) POD enzyme activity assay

[0097] First, sodium acetate (NaAc) powder was dissolved in deionized water to prepare a 1.0 M NaAc solution, which was then added to glacial acetic acid to form a NaAc-Hac buffer solution with a pH of 4.0 and a final concentration of 0.1 M;

[0098] Then prepare H2O2 solutions with final concentrations of 1mM, 10mM, 20mM, 30mM, and 40mM and TMB solution with a concentration of 10mM;

[0099] Finally, 20 μL of different concentrations of MoS2-LC@Gal (C1=7.8125 μg / ml, C2=15.625 μg / ml, C3=31.25 μg / ml, C4=62.5 μg / ml, C5=125 μg / ml, C6=250 μg / ml, C7=500 μg / ml, C8=1000 μg / ml), 40 μL of TMB solution and 20 μL of H2O2 were mixed, and 0.1 M NaAc-Hac buffer was added to form a 4 mL system. The system was incubated at 37°C in the dark for 30 min, the color changes were observed and recorded, and the absorbance of different groups was measured at a wavelength of 652 nm using a UV spectrophotometer.

[0100] The results show that ( Figure 3 ), when the hydrogen peroxide concentration is fixed at 20 mM, as the concentration of MoS2-LC@Gal nanozyme increases, the absorption peak at 652 nm after the reaction becomes more significant, and the color change of the solution is also more obvious. This shows that the nanozyme synthesized by the present invention has good POD activity, and it is concentration-dependent.

[0101] (2) Ductility and viscosity

[0102] The prepared SNCI@MLG was adhered to the oral mucosa, large intestine, small intestine, heart, and stomach of rats and suspended in the air. The results showed that it could adhere well to the above organs. After SNCI@MLG was placed in the rat periodontium, it was flushed with a syringe. The results showed that it could be well retained in the rat periodontium. In addition, an appropriate amount of the prepared SNCI@MLG was placed on the upper side of the finger. After bending the finger, SNCI@MLG was able to stretch with the angle of the finger bending, indicating that it has good ductility ( Figure 6 ).

[0103] (3) Antibacterial properties

[0104] The antibacterial biological activity of N-CC and N-CC-IL was evaluated by bacterial morphology, survival test, live-dead staining and colony counting test. Porphyromonas gingivalis (P.gingivalis, Pg) was evenly spread on TSB medium supplemented with hematin, vitamin K and sheep blood after the preparation, and cultured under standard anaerobic conditions (5% H2, 15% CO2, 80% N2, 37°C).

[0105] Bacterial morphology was observed by scanning electron microscopy (Thermo Fisher Scientific Quattro S, USA). After incubating the bacteria with the preparation and the collected rat periodontal bacterial suspension for 2 h, the samples were fixed in glutaraldehyde (2.5%) for 2 h and then dehydrated in a gradient ethanol series for 10 min. Finally, after drying and spraying with gold powder, the morphology and integrity of the bacteria were observed by scanning electron microscopy.

[0106] Plate coating experiment results ( Figure 7 ) showed that the number of bacteria in the N-CC-IL group was significantly lower than that in the N-CC group, indicating that N-CC-IL can effectively inhibit bacterial proliferation. SEM results showed that compared with the N-CC group, the bacteria in the N-CC-IL group shrank a lot (red arrows in the figure), the membrane integrity was damaged, and significant deformation, collapse and fracture occurred ( Figure 8 ).

[0107] (4) Ferrous ion adsorption

[0108] Periodontal ligament stem cells were collected at 2×10 5 The cells were inoculated into a laser confocal microscopy dish and cultured overnight in a 5% CO2, 37°C incubator. After complete attachment and stimulation for 24 hours, MoS2 and MoS2-LC were added respectively and cultured for 48 hours. The culture medium was discarded and the ferrous ion fluorescent probe cells were incubated for 30-60 minutes. The culture medium was discarded and the fluorescence intensity of each group was observed under a laser confocal microscope.

[0109] The experimental results showed that compared with the MoS2 group, the orange-yellow fluorescence intensity representing the concentration of ferrous ions in the MoS2-LC group decreased significantly, indicating that the level of ferrous ions decreased significantly ( Fig. 9 ). Therefore, after MoS2 is grafted with cysteine, the concentration of ferrous ions can be reduced.

[0110] Test Example 2: Pharmacodynamics Experiment

[0111] (1) Establishment of experimental periodontitis rat model and drug administration

[0112] 90 SD rats were purchased and silk thread ligature was used to induce experimental periodontitis rat model. The rats were anesthetized with sodium pentobarbital (1%, 30 mg / kg) and placed on the operating table to fully expose their maxillary molars. A 0.22 mm ligature was tied in the subgingival area between the first and second maxillary molars. After fixation for 2 weeks, the experimental periodontitis rat model was established. The experimental periodontitis rats after successful modeling were divided into 6 groups (n=8): Model group (normal saline was given after ligation), MoS2-LC@Gal group (MoS2-LC@Gal was given after ligation), SNCI@MLG group (SNCI@MLG was given after ligation), SNCI@MLG+L group (SNCI@MLG was given after ligation and light was applied), and the Normal group was not treated. The drug was administered every other day, and the maxillary molars and blood of all rats were collected on the 28th day.

[0113] (2) ELISA to measure inflammation level

[0114] In order to determine the effect of the preparation on the inflammation level of rats with periodontitis, the tissues around the first and second molars of the rats were collected and ground with a glass grinder and centrifuged to obtain the supernatant for the determination of inflammation level. The levels of TNF-α, CXCL-1, and IL-10 in the tissues were quantified using ELISA kits.

[0115] The results showed that silk ligation combined with LPS could induce a local inflammatory microenvironment, with high levels of CXCL-1 and TNF-α ( Fig.10). Compared with the Model group, the levels of pro-inflammatory factors CXCL-1 and TNF-α in the SNCI@MLG group were significantly decreased after treatment (P<0.001), and the level of anti-inflammatory factor IL-10 was increased (P<0.01). In addition, the ability of MoS2-LC@Gal to reduce the levels of pro-inflammatory factors CXCL-1 and TNF-α was lower than that of SNCI@MLG.

[0116] (3) Tissue staining and immunohistochemistry

[0117] The right maxillary teeth of rats in each group were completely immersed in 4% paraformaldehyde for 48 hours, and then the samples were decalcified with EDTA at room temperature for four weeks. After paraffin embedding and sectioning, hematoxylin-eosin (HE) was used for histological observation. In addition, the paraffin sections were dewaxed with xylene and hydrated with different concentrations of ethanol gradient. After washing with PBS, they were treated with 3% hydrogen peroxide solution at room temperature for 20 minutes to remove endogenous peroxidase activity. In order to block nonspecific binding, the sections were blocked with 5% bovine serum albumin (BSA) in PBS for 1 hour. For immunofluorescence experiments, after the sections were incubated with the target antibody overnight, they were washed with PBS 3 times and the corresponding fluorescent secondary antibody was added, incubated in the dark for 1 hour, and finally the cell nuclei were stained with DAPI and sealed.

[0118] Experimental results ( Fig.11 ) showed that the gingival tissue showed obvious inflammatory response in the model group. First, in the gingival connective tissue layer, the infiltration of inflammatory cells was more prominent, the periodontal tissue structure changed significantly, and the papilla disappeared, indicating the presence of acute or chronic inflammatory response. In the SNCI@MLG group, the infiltration of inflammatory cells decreased and the periodontal tissue partially regenerated. GPX4, FTH1 and ACSL4 are key proteins in the occurrence and development of ferroptosis. Immunofluorescence results showed that in the periodontal tissue of the model group, the expression of GPX4 decreased significantly, especially in areas with more active inflammatory responses, while the expression of FTH1 and ACSL4 increased. In the SNCI@MLG group, the expression of GPX4 increased, and the expression of FTH1 and ACSL4 was inhibited, thereby reducing the occurrence of ferroptosis in cells; in addition, the ability of MoS2-LC@Gal to reduce the levels of ferroptosis-related proteins was significantly lower than that of SNCI@MLG.

Claims

1. A method for preparing a multifunctional nanozyme composite hydrogel, characterized in that: The steps include: (1) Molybdenum disulfide MoS2 was synthesized using hexaammonium heptamolybdate tetrahydrate and thiourea as raw materials; (2) stirring and reacting MoS2 with cysteine ​​to obtain MoS2-LC; (3) Mixing galangin with MoS2-LC, and stirring to react after ultrasonication to obtain MoS2-LC@Gal; (4) adding acetic anhydride to the carboxymethyl chitosan aqueous solution to obtain N-acetylated carboxymethyl chitosan N-CC; (5) Add 1-butyl-3-methylimidazolium chloride to N-CC for reaction, and precipitate with alcohol to obtain N-CC-IL; (6) The crosslinker, MoS2-LC@Gal and N-CC-IL are blended to obtain SNCI@MLG.

2. The method for preparing the multifunctional nanozyme composite hydrogel according to claim 1, characterized in that: In step (2), the mass ratio of MoS2 to cysteine ​​is 1:3-10.

3. The method for preparing the multifunctional nanozyme composite hydrogel according to claim 1, characterized in that: The specific steps of step (3) are: dissolving MoS2-LC in water to form liquid A, dissolving galangin in a co-solvent to form liquid B, mixing liquid A and liquid B, and stirring to react after ultrasonication to obtain MoS2-LC@Gal.

4. The method for preparing the multifunctional nanozyme composite hydrogel according to claim 3, characterized in that: The co-solvent is methanol: water = 1: 1, ethanol: water = 1: 1 or dichloromethane: water = 1: 1; the ultrasonic time is 20-40 minutes.

5. The method for preparing the multifunctional nanozyme composite hydrogel according to claim 1, characterized in that: In step (4), the mass ratio of the carboxymethyl chitosan to acetic anhydride is 1:2-6.

6. The method for preparing the multifunctional nanozyme composite hydrogel according to claim 1, characterized in that: In step (5), the mass ratio of N-CC to 1-butyl-3-methylimidazolium chloride is 1:1-10.

7. The method for preparing the multifunctional nanozyme composite hydrogel according to claim 1, characterized in that: In step (5), the reaction conditions are 60° C.-80° C. and nitrogen for 36-72 hours.

8. The method for preparing the multifunctional nanozyme composite hydrogel according to claim 1, characterized in that: In step (6), the cross-linking agent is one or more of azobenzene, 4-(4-methoxyphenylvinyl)pyridine, selenocystamine or 7-diethylamino-4-thiocoumarylmethyl derivatives.

9. A multifunctional nanozyme composite hydrogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the multifunctional nanoenzyme composite hydrogel according to claim 9 in the preparation of a drug for treating periodontitis.

Citation Information

Cited By

  • MoO3-X nano-enzyme composite hydrogel as well as preparation method and application thereof

    CN122399097A